On the FFT-based homogenization of cohesive zones: An application to the fiber-matrix composite core of metal sandwich plates - Bödeker, Felix Christian; Justus Liebig University Giessen (My University, 2026)
Advanced, lightweight materials with good structural performance and advantageous fracture behavior, such as HybrixTM sandwich plates with a composite core (Lamera AB, Gothenburg, Sweden), are essential for various industries. They enable the reduction of energy consumption, which makes them crucial in the fight against climate change. However, these materials are often complex and highly adaptable to the desired industrial applications. Hence, a full experimental characterization of the fracture behavior can be time-consuming and costly. For example, the sandwich core, which largely defines the fracture behavior of the entire plate, consists of polymer fibers and binder as well as a large amount of porosity. Computational homogenization techniques can significantly reduce this experimental effort for the development of advanced engineering materials. In this approach, a virtual model for the microstructure of the material of interest is generated. Then, with the known material models of the constituents, effective macroscopic properties are obtained using computational methods. Compared with the classical Finite Element Method (FEM), which is commonly used for this purpose, solvers based on the Fast Fourier Transform (FFT) can significantly reduce the (computational) effort needed. Nevertheless, the classical approaches cannot be applied straightforwardly to fracture behavior. Material layers, such as the composite core, can be modeled as a cohesive zone with a finite thickness, which allows for accounting for the fracture behavior with specialized computational methods. Building on such an existing classical FEM-based method, this work introduces a novel FFT-based homogenization scheme for cohesive zones, which extends the application of the FFT methods to fracture behavior. The novel FFT solver uses a displacement-based Barzilai-Borwein scheme and a non-local ductile damage model for the fracture behavior. In addition, an innovative micromechanical modeling approach for the fracture behavior of the sandwich core is presented. It combines a novel method for the virtual microstructure generation for the composite core with the FFT-based homogenization scheme for cohesive zones. Furthermore, the parameters of the elastic-plastic material model including a non-local, ductile damage model were identified using microindentation and mode I tests (Double Cantilever Beam). The novel modeling approach, along with the FFT-based homogenization scheme for cohesive zones, was furthermore experimentally validated using mode III tests (Split Cantilever Beam). Hence, this modeling Approach lays the foundation for an extension to other material layers, e.g., adhesives.
Keywords: ddc:620